Der Strafkläger im Strafbefehls- und im abgekürzten Verfahren - Oehen, Moritz (sui generis, 2019)
The present work provides an overview of the role that victims play as prosecutors, irrespective of material compensation interests in criminal proceedings. The party rights of the criminal prosecutor are treated in the same way as his position in the efficient penal and abbreviated procedures. In doing so, inconsistencies in the law are discussed, the previous case law on the criminal prosecutor critically questioned and the conflicting goals between injured party participation and procedural efficiency examined. The role of the criminal prosecutor in Swiss jurisprudence has so far only been examined selectively and always with regard to specific issues. For the first time, the author attempts to broach the issue of the criminal prosecutor as a litigant and to put it into context with the idea of ​​efficiency that characterizes criminal procedural law.